(untitled) (Tarombo: Journal of Christian Theology, Education, and Ministry, 2026)
This study examines the leadership model of the father in Luke 15:11–32, focusing on the often-overlooked perspective of the elder son. While existing scholarship predominantly centers on the prodigal son, the elder son’s experience of faithfulness and perceived neglect presents a critical tension for leaders balancing justice and mercy. The research addresses the problem of dichotomous leadership in religious and social organizations, where leaders struggle to integrate procedural fairness with relational compassion. Employing a qualitative hermeneutic approach to the biblical narrative and a critical review of leadership theories—including transformational, servant, organizational justice, and agape love frameworks—the study identifies a research gap in integrative models. The novelty lies in proposing the Parental Justice-Mercy Integration (PJMI) Framework, which synthesizes three dimensions: restorative justice, unconditional love, and recognition of faithfulness. Preliminary analysis suggests that the father’s simultaneous affirmation of the elder son’s loyalty (Luke 15:31) and restoration of the younger son demonstrates a non-dichotomous leadership model. This framework offers a contextual contribution for Christian leaders in Indonesia facing cultural pressures of paternalism, providing a practical tool to navigate justice-mercy tensions without sacrificing either principle. Keywords: leadership; justice; mercy; elder son; Luke 15; PJMI Framework ABSTRAK Penelitian ini mengkaji model kepemimpinan Bapa dalam Lukas 15:11–32, dengan fokus pada perspektif anak sulung yang sering terabaikan. Sementara studi sebelumnya mayoritas berpusat pada anak bungsu, pengalaman anak sulung tentang kesetiaan dan perasaan tidak dihargai menghadirkan ketegangan kritis bagi pemimpin yang menyeimbangkan keadilan dan kasih. Penelitian ini menjawab masalah kepemimpinan dikotomis di organisasi keagamaan dan sosial, di mana pemimpin kesulitan mengintegrasikan keadilan prosedural dengan kasih relasional. Menggunakan pendekatan hermeneutik kualitatif terhadap narasi Alkitab dan tinjauan kritis atas teori kepemimpinan, termasuk transformasional, servant, keadilan organisasional, dan kasih agape—studi ini mengidentifikasi celah riset dalam model integratif. Kebaruan terletak pada pengajuan Parental Justice-Mercy Integration (PJMI) Framework, yang mensintesis tiga dimensi: keadilan restoratif, kasih tanpa syarat, dan pengakuan atas kesetiaan. Analisis awal menunjukkan bahwa tindakan Bapa yang secara simultan menegaskan kesetiaan anak sulung (Lukas 15:31) dan memulihkan anak bungsu menawarkan model kepemimpinan non-dikotomis. Kerangka ini memberikan kontribusi kontekstual bagi pemimpin Kristen di Indonesia yang menghadapi tekanan budaya paternalistik, sebagai alat praktis untuk menavigasi ketegangan keadilan-kasih tanpa mengorbankan salah satu prinsip. Kata kunci: kepemimpinan; keadilan; kasih; anak sulung; Lukas 15; PJMI Framework